Legal Consequences of the Marriage Agreement Made by Notaries, Then Not Registered - Meisha Poetri Perdana (Authentica, 2019)
The marriage agreement is based on Law Number 1 of 1974 Concerning Marriage, a marriage agreement is a means of protecting the assets of a husband and wife, this agreement the parties can determine their respective inheritance. Is there a separation of assets in the marriage from the beginning or is there a shared asset, but the method of division is divided if a divorce occurs. The inheritance of each husband and wife and property obtained as a gift or inheritance, respectively, is under the control of each other as long as the parties do not specify otherwise. The method used in this research is the normative juridical approach. The data used in this paper are secondary data and primary data as a complement to secondary data. The results of research and discussion, namely the marriage agreement that is not recorded or registered, is invalid according to the provisions of Article 29 paragraph (1) of Law Number 1 of 1974. The legal consequences of marital property if the marriage agreement is not registered is that the property becomes joint property and assets default. Legal protection for a disadvantaged third party is by means of preventive legal protection in which a third party has the right to assume that the marriage agreement does not exist, whereas the refractive legal protection that is the third party has the right to file a lawsuit in court. Suggestions that the notary provides guidance to register the marriage agreement deed to the Population and Civil Registry Office in order to obtain validity and publicity. And the marriage agreement must be registered so as not to harm a third party. Keywords: Registration of Marriage Agreement, Marriage Property, Legal Protection of Third Party